PENGARUH INTENSITAS MENONTON PROGRAM SIARAN MATA NAJWA TERHADAP PENGEMBANGAN WAWASAN MAHASISWA ILMU POLITIK UIN ALAUDDIN MAKASSAR (Fakultas Dakwah dan Komunikasi, 2020)
This study aims to determine the effect of the intensity of watching the Mata Najwa broadcast program on the development of insight of political science students at UIN Alauddin Makassar and to find out how much influence the intensity of watching the Mata Najwa broadcast program has on the development of insight into political science students of UIN Alauddin Makassar. Using explanatory research (explanatory research) with a quantitative research approach. The results of the study indicate that; The influence of the intensity of watching the Mata Najwa broadcast program on the development of insight of Political Science students at UIN Alauddin Makassar can be seen in the t-test results, it is known that t count the intensity of watching (17,236)> from t table (2,000) or sig (0,000) <alpha (0.05 ) is a significance of 5%, thus H0 is rejected and Ha is accepted. Based on the results of this statistical test, shows that the viewing intensity factor has a significant relationship with the development of insight into the political science students of UIN Alauddin Makassar. The effect of the intensity of watching the Mata Najwa broadcast program on the development of insight of Political Science students at UIN Alauddin Makassar through a simple linear regression test shows that the R Square value is 0.846. This means that the intensity of watching the Mata Najwa broadcast program has an influence of 84.0% on the ability to develop the insight of Political Science students at UIN Alauddin Makassar.